Resolution (proposed) - Hicks,George, M.P.
1936-09-25 Attach to a letter to Stolz I.F.T.U. RESOLVED that this International Conference of Trade Unionists and Socialists express keenest admiration for and sympathy with their Spanish comrades in their heroic struggle against the forces of Fascism and Dictatorship, and decide to appoint herewith a deputation adequately representative of the Trade Union National Centres and International Secretariats, with a view to conferring with them and making such enquiries as will enable the continued administration of relief to be organised, with the object of assisting in the complete victory for freedom and democracy. 292/946/10/90